En Coup De Sabre in 16-Year-Old Girls: A Case Report - Gardenia Akhyar; Fauzana Nazifah; Ennesta Asri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: En coup de sabre (ECDS) is one of the clinical variations of morphea. ECDS refers to a variant of linear morphea that usually involves the forehead and frontal scalp that may be associated with alopecia. This study aimed to describe a case of en coup de sabre with its diagnosis and management. Case presentation: A girl, aged 16 years, came to the dermatology polyclinic with the main complaint of a sunken brown spot on the left forehead and corner of the left eye, which has been expanding since 2 months ago. This complaint does not feel itchy or painful, but because it is getting more widespread, patients feel embarrassed and often cover it up. On dermatological examination, depressed hyperpigmented macules, plaque size, firm boundaries, and location on the left medial superior lid and left medial glabella were found. On dermoscopy examination, a reticular pigment network obliterating the follicular opening was found. The results of the histopathological examination showed the impression of a linear morphea type with en coup de sabre. This patient was diagnosed with linear morphea type with en coup de sabre Conclusion: En coup de sabre is a rare autoimmune disorder and is a subtype of morphea. Early detection and appropriate intervention will reduce disease progression.